MUI dan Nalar Fatwa-fatwa Eksklusif - . Iswahyudi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2016)
The Indonesian Ulama Council (MUI) as a religious organization which is established by the state should be as guardiance for indonesian plurality. One plurality is various Muslims. This article explains that many MUI fatwas produced exclusively. Those fatwas can bring out a radicalism behavior. Those fatwas such the fatwa on Syi’ah, Ahmadiyah and pluralism-liberalism-secularism. This article shows a lot of data about radicalism with the justification of those fatwas. According to the authors, the MUI fatwas lead to exclusivism. As the reason, the using of baya>ni> epistemology which is evidenced by the revelation understanding textually, then exploration of subordinated sense; the using of deductive logic and kalam argument and maslahat theocentric reason. As the result, the authors suggests to construct MUI be structuralized and have inclusive paradigm and tafsi>li> formulation of fatwas. It means fatwas give many legal alternatives as well as the tradition of previous scholars